A Validation of the Ultrasound Wave Velocity Method to Predict Porosity of Dry and Saturated Cement Paste - Zhenting Zou; Jay N. Meegoda (Advances in Civil Engineering)
An approximate theoretical validation of the measured variation of ultrasound velocity with porosity of dry and saturated cement paste is proposed using finite element analysis of cement paste assuming as a multiphase composite. Cement paste is a multiphase composite consisting of solid cement and microscopic voids filled either with air or water. The void content in cement paste is directly related to strength and durability. Experimental tests showed that ultrasound wave velocity is decreased with the increase in porosity of cement paste, where pore sizes are similar in dimension to the wavelength of the sound enabling ultrasound to be used as a potential condition assessment technique. However, the variation of ultrasound wave velocity also depends on the fluid in the voids. Several finite element simulations using two commercially available software packages were performed for both fully saturated and dry blocks of cement paste with different porosities. Then back-calculated elastic moduli values from finite element simulations were used to compute the wave velocities of both fully saturated and dry cement paste with different porosities. The predicted ultrasound velocities with porosity for both dry and saturated cement paste are compared well with the laboratory measurements.